The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3991/ijet.v16i24.27835
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of an Intelligent Online English Learning System Based on Mobile Internet Technology

Abstract: A predicament facing education is that the traditional teaching mode could no longer meet the requirements of modern society. The fast development of mobile Internet technology has brought online education platforms into existence, and these newborn things are very helpful to solve the mentioned contradiction. To deepen the research of the application of mobile Internet technology in modern education, this paper designed the functional modules of an intelligent online English teaching (IOET) system and impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…These findings are contradicted by a comprehensive evaluation of 29 research that found mobile learning to be as successful as, if not more effective than, conventional learning (Dunleavy et al, 2019). Liu & Yan (2021) reported the use of an intelligent online English learning system based on mobile internet technology. However, students may see how to do practical skills and learn theoretical information through interactive websites/apps since they are adaptable, accessible, and transparent.…”
Section: Discussionmentioning
confidence: 92%
“…These findings are contradicted by a comprehensive evaluation of 29 research that found mobile learning to be as successful as, if not more effective than, conventional learning (Dunleavy et al, 2019). Liu & Yan (2021) reported the use of an intelligent online English learning system based on mobile internet technology. However, students may see how to do practical skills and learn theoretical information through interactive websites/apps since they are adaptable, accessible, and transparent.…”
Section: Discussionmentioning
confidence: 92%
“…For example, the development and implementation of platforms like U-Msg emphasize the need for such comprehensive approaches. Such research would not only benefit EFL educators in making informed decisions but also assist app developers in refining and enhancing their offerings (Katsarou et al 2023;Liu and Yan 2021;Gren 2020;Ongoro and Fanjiang 2023;Alieto et al 2020). In conclusion, the ultimate aim of this line of inquiry is to optimize the EFL learning experience.…”
Section: Introductionmentioning
confidence: 99%
“…The field of English as a Foreign Language (EFL) has experienced a notable increase in the creation and utilization of educational applications that aim to provide personalized and flexible learning experiences, catering to the varied requirements and learning preferences of EFL learners (Kaharuddin 2022;Liu and Yan 2021;Gren 2020;Ongoro and Fanjiang 2023;Han and Niu 2021). The importance of E-learning has been emphasized, particularly in times of disruption such as the COVID-19 pandemic, underscoring its crucial role in sustaining and improving English proficiency among students (Kaharuddin 2022) With the advent of intelligent virtual agents, they've been integrated into EFL learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developments in recent decades have changed the traditional social and educational structures, and technology has played a significant role in the educational context [24]. With the change in social education and the advance of information technology, people working in the educational field have adapted and adjusted their conventional teaching and learning approaches [25,26]. Thus, for the younger generation, studying mathematics should promote meaningful learning to students, with an emphasis on mathematics comprehension to develop the skills that are essential in the twenty-first century to be competitive internationally [10,16].…”
Section: Introductionmentioning
confidence: 99%